When researchers in teacher education and training other: Social justice and the “migrant student” in an EU–Finland project - Lukala, Ella-Maria; Dervin, Fred (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2026)
This article investigates the positioning of the “migrant student” in an EU–Finland project which aims to prepare teachers for social justice “migrant education.” Since the project is produced in and for a neoliberal economic-political supranational institution, the authors seek to examine the potential contradictions between the frameworks of social justice and neoliberalism in documents produced by the project teams. The results show that the migrant student is othered and mostly positioned as different, disadvantaged, and problematic. The implications of othering are thus addressed, with recommendations made for ethical treatment of the other in research and education while urging, for example, funding institutions and individual scholars to recognize and address academic othering in the Nordics and beyond.